The night and day of dung beetles (Coleoptera, Scarabaeidae) in the Serra do Japi, Brazil: elytra colour related to daily activity - Hernández, Malva Isabel Medina [UNESP] (Sociedade Brasileira de Entomologia, 2002)
In the present study 387 dung beetles (Coleoptera: Scarabaeidae) were surveyed at the Serra do Japi, in the Atlantic Forest in São Paulo State, with four baited pitfall traps during the months of December, 1998, and January, 1999 during eight 24 hour cycles. A total of 30 species were identified and temporal variation in activity patterns among the species shows a specialization in the use of food resources: 9 species were classified as nocturnal and 13 as diurnal. The daily activity pattern of dung beetles does not necessarily correspond to the taxonomic classification, but is strongly related to the colouring of species, determined by predominant elytra colour: nocturnal species have 89 % more chances of being black as opposed to colourful. Black nocturnal species might have evolved as an interspecific adaptation to avoid predation (cryptic colouring). Among the colourful diurnal dung beetles, measure of body length of each species shows that development of bright colouring was more often found in medium to large species, which suggests that colouring evolved as a response to intraspecific pressures, important in agonistic encounters among males.
Keywords: Coleoptera; colour; daily activity; dung beetles; Scarabaeidae